“Assessing the Relationship between Financial Technology (FinTech) Implementation and Financial Performance: Evidence from NSE-Listed Banks in India” (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: Using digital innovations such as cloud computing, blockchain, big data analytics, mobile banking, and artificial intelligence to deliver financial services is known as Financial Technology (FinTech). FinTech prioritizes speed, accessibility, and user-centric design in contrast to traditional systems. This study examines the impact of Financial, Technology (FinTech) adoption on the financial performance of 32 public and private sector banks listed on the NSE in India from 2015–2016 to 2024–2025. FinTech tools such as mobile banking, credit/debit cards, UPI, AI, and blockchain have transformed India’s banking system by enhancing efficiency, accessibility, and customer experience, while also posing challenges in cybersecurity, regulation, and restructuring. The research uses a quantitative, descriptive design with secondary data from RBI, the World Bank, and banks’ annual reports, applying descriptive statistics, correlation, and regression analysis. FinTech adoption is measured through transaction-based indicators (mobile, credit, and debit usage), with bank size, GDP, and inflation as control variables. Findings indicate that FinTech adoption significantly improves financial performance. Mobile banking enhances capital adequacy and earnings through efficiency gains, while card usage strengthens liquidity and profitability via increased transactions and fee income. GDP growth further boosts bank performance, whereas inflation has mixed effects on asset quality and liquidity. Private banks, being more technologically agile, show faster adoption and better results compared to public banks, which face legacy infrastructure and administrative hurdles.